Monitoring Forest Health Based on Species Diversity Parameters Around Way Kalam Waterfall Tourism Area - Dini Ratna Sari; Rahmat Safe'i; Machya Kartika Tsani (Pattimura University Ambon Maluku Indonesia, 2026)
This study aims to assess forest health based on species diversity indicators around the Way Kalam Waterfall tourism area in Penengahan, South Lampung. The Forest Health Monitoring (FHM) method was applied using four cluster plots to evaluate the condition of vegetation through measurements of species diversity, composition, and the structure of tree communities. The results showed that the Shannon-Wiener diversity index (H’) in all clusters was categorized as low, indicating a homogeneous vegetation structure and dominance of several species. Despite the low diversity values, the final forest health scores (NKH) revealed that three clusters were classified as “Good,” while one cluster fell into the “Poor” category due to higher ecological pressure and reduced species variation. These findings demonstrate that although the forest ecosystem is still functioning, it is experiencing biodiversity decline, which may affect long-term ecological stability. Therefore, biodiversity indicators remain essential for detecting early ecological disturbances, particularly in tourism areas that are vulnerable to human activities. The study concludes that effective management strategies, including vegetation enrichment, controlled tourism activities, and regular forest health monitoring, are necessary to maintain ecological resilience and support sustainable forest conservation.